Immunoglobulin Fc-Fused Peptide without C-Terminal Arg or Lys Residue Augments Neuropilin-1-Dependent Tumor Vascular Permeability - Baek, Du San; Kim, Jeong Ho; Kim, Ye Jin; Kim, Yong Sung (Molecular Pharmaceutics, 2018)
Neuropilin-1 (NRP1), which functions as a coreceptor for vascular endothelial growth factor (VEGF) and is implicated in vascular permeability and tumorigenesis, has been targeted by peptides that specifically bind to the VEGF-binding region on NRP1. Like natural VEGF ligands, all known peptides with NRP1-binding activity bind only through a carboxy (C)-terminal R/K-x-x-R/K sequence motif (x stands for any amino acids); this strict requirement is called the C-end rule (CendR). Here, we report immunoglobulin Fc-fused NRP1-specific peptides deviating from CendR. We screened a yeast surface-displayed Fc-fused non-CendR peptide library against NRP1 and isolated Fc-V12, wherein V12 peptide comprising 12 amino acids has a PPRV sequence at its C-terminal end. Although Fc-V12 lacked the CendR motif, it showed selective binding to the VEGF-binding region of NRP1 and triggered cellular internalization of NRP1, which resulted in enhanced extravasation into tumor tissues and tumor tissue penetration of the Fc-fused peptide along with the coinjected chemical drug in tumor-bearing mice. Through a saturation mutagenesis study, we identified that the Val residue at the C-terminus of Fc-V12 is crucial for NRP1 binding. We further improved NRP1 affinity of Fc-V12 (K D = ∼761 nM) through directed evolution of the upstream sequence of PPRV to obtain Fc-V12-33 (K D = ∼17.4 nM), which exhibited enhanced NRP1-mediated vascular permeability as compared with Fc-V12. Our results provide functional Fc-fused non-CendR peptides, which bind to the VEGF-binding region of NRP1 and enhance vascular permeability, expanding the sequence space of NRP1-targeting peptides.
Keywords: Animals; Capillary Permeability; Carcinogenesis; Cell Line, Tumor; Female; Humans; Immunoglobulin Fc Fragments; Ligands; Mice; Mice, Inbred BALB C; Mice, Nude; Mutagenesis; Neoplasms; Neuropilin-1; Peptides; Protein Binding; Recombinant Fusion Proteins; Vascular Endothelial Growth Factor A; Xenograft Model Antitumor Assays; C-end rule; neuropilin-1; peptide engineering; vascular permeability; yeast surface display